Impact of environmental conditions on the performance of open multideck display case evaporators - Heidinger, Gustavo Galdi (2019)
This paper reports the results of experimental tests performed according to ISO 23953 in an open multideck display case with dual air curtain in order to evaluate the impact of environmental conditions on the performance of its evaporator. Experimental laboratory tests were performed on two climate classes usually found in Brazilian food stores (n.º 3: 25ºC and 60% and n.º 6: 27ºC and 70%). In either test the maximum product temperature was maintained between 4 and 5°C. The experimental results comparison shows the quantitative variation of the frost formation rate on the evaporator coil (+37%) and how this phenomenon affects the distribution and magnitude of air flow, pressure drop, inlet and outlet temperatures and the components of the total sensible (+10%) and latent (+46%) heat loads. The analysis of experimental data provides valuable information to the evaporator design based on in-store environmental conditions.